Advertisements
Advertisements
प्रश्न
f(x) = 4x4 − 3x3 − 2x2 + x − 7, g(x) = x − 1
उत्तर
Let us denote the given polynomials as
`f (x) = 4x^4 - 3x^3 - 2x^2 + x - 7`
`g(x) = x-1`
We have to find the remainder when f(x) is divided byg(x).
By the remainder theorem, when f(x) is divided by g(x) the remainder is
`f(1) = 4(1)^4 - 3(1)^3 - 2(1)^2 + 1-7`
` = 4 - 3- 2 + 1- 7`
` = -7`
Now we will show remainder by actual division
So the remainder by actual division is −7
APPEARS IN
संबंधित प्रश्न
f(x) = x3 − 6x2 + 2x − 4, g(x) = 1 − 2x
Show that (x − 2), (x + 3) and (x − 4) are factors of x3 − 3x2 − 10x + 24.
Show that (x + 4) , (x − 3) and (x − 7) are factors of x3 − 6x2 − 19x + 84
For what value of a is (x − 5) a factor of x3 − 3x2 + ax − 10?
Factorize of the following polynomials:
x3 + 13x2 + 31x − 45 given that x + 9 is a factor
Write the remainder when the polynomialf(x) = x3 + x2 − 3x + 2 is divided by x + 1.
If both x − 2 and \[x - \frac{1}{2}\] are factors of px2 + 5x + r, then
Factorise the following:
a2 + 10a – 600
Factorise the following:
5x2 – 29xy – 42y2
Factorise:
2x3 – 3x2 – 17x + 30